Informed dissent: the views of some mothers of severely mentally handicapped young adults. Issue 2 (June 1986) - Simms, M
Abstract : Much of the discussion since the Arthur case has centred round the rights of handicapped infants to medical treatment. Little has centred round the question of how far one person can rightly be required to sacrifice her life for another, when she has not been consulted beforehand. This may be due to the fact that most of the discussants are men, while nearly all the carers are women. This small study attempts to redress this balance by asking mothers who have cared for 20 years, whether they felt it was worthwhile.